THE USE OF BRAINSTORMING METHODS IN IMPROVING THE ARABIC SPEAKING SKILLS (AN EXPERIMENTAL RESEARCH IN GRADE III OF SMP IT ZURRIYATUL QUR'ANI AL-MA'ARIF): تطبيق طريقة العصف الذهني لترقية مهارة الكلام (دراسة تجريبية في الفصل الثالث بالمدرسة المتوسطة ذرية القرآن المعارف) - Putri Rambe, Rika (Institut Agama Islam Negeri Lhokseumawe, 2023)
This Article is entitled the use of brainstorming methods in improving the Arabic speaking skills. The purpose of this study is to determine the effectiveness of the application of brainstorming methods to improve the speaking skills in grade III of SMP IT Zurriyatul Qur'ani Al-Ma'arif. This research is an experimental research with one group pre-test, post-test design. The population of this study is all students at SMP IT Zurriyatul Qur'ani Al-Ma'arif. And the sample is grade III students as an experimental class with a total of 14 students. The results of the study were obtained by using the observation sheet when applying the brainstorming method to improve the ability to speak Arabic which indicates very good / good scores, as stated on the test sheet (Pretest-posttest). The research results in this study showed a significant level (2-tailed). 000<0.05 after the T test using the